Bike-sharing, car-sharing, e-scooters, and Uber: Who are the shared mobility users and where do they live?. (November 2022) - Mouratidis, Kostas
Highlights: Bike-sharing users are worried about change, while Uber users are less worried. Car-sharing is strongly associated with lack of access to a private car. Shared mobility users are likely to reside in central, denser, transit-oriented locations. Bike-sharing users live closer to the city center than other shared mobility users. Citizens without tertiary education more likely to use shared e-scooters and Uber. Abstract: This research provides new evidence on factors associated with the use of four different shared mobility options – bike-sharing, e-scooter sharing, car-sharing, and ridehailing (Uber) – in the same urban region. Factors examined are sociodemographic characteristics, concern about climate change, access to a private car, and built environment characteristics of users' residential locations. The analyses are based on survey and GIS-measured, individual-level geospatial data from Oslo and its surrounding Viken county in Norway. Findings suggest that bike-sharing users are more likely to be younger, men, single, concerned about climate change, and living in denser neighborhoods with good access to public transport. E-scooter sharing users are more likely to be younger, men, without disabilities, and less educated, and live in denser neighborhoods. Car-sharing users are more likely to be living with a partner or spouse and children, not have access to a private car, and live in transit-oriented neighborhoods. Uber users are more likely to be younger and less educated, have higher incomes, be less worried about climate change, and live in proximity to the city center. These outcomes offer input for critical issues of urban and transport planning including compact urban form, sustainable mobility, and transport equity.